Research of factors affecting thickness of the covering obtained by electro contact sintering of composite materials. (February 2019) - Markov, V; Sokolova, V; Rzhavtsev, A; Eliseev, I
Abstract: This article is devoted to research of qualitative characteristics of composite materials, and it includes the introduction, the technique of research, the results of research and the basic conclusions. In the introduction, the urgency of the theme is substantiated, and the object and research problems are formulated. In the research technique, the factors directly affecting the thickness of the covering are revealed, research is carried out, experiments are set up. The impulse and pause times are chosen so that the covering had enough time to conglomerate, whilst there was no burning out of the composite material and the unit's overheating was also avoided. The pressure of a roller clip should guarantee a uniform covering however without allowing the powder material to be expelled from the sintering zone. Powder PK40C2, in its mass structure consisting of: iron - more than 96 %; carbon – 0, 3-06%; chrome – 1-3%, will be the material to be tested. Based on the conditions of the experiment the planning matrix is built, and after processing the matrix, the regress equation is obtained. In order to assess the uniformity of the equation dependences obtained, Kohren's criterion was used; for verification of the importance of the polynom members - Student's criterion was used, and for verification of the adequacy of the equation of the regression - Fisher's criterion was used. As a result of the research, the diagram of dependence of the covering thickness upon impulse and pause time is constructed; quantity of the heat emitted in burning of the composite material is calculated. In the course of research, the optimum modes of applying the covering and their parametrical influence on the thickness of the covering were estimated. Recommendations regarding applying the composite covering by a method of electro-contact method were given. Dependences of the impulse and pause time to the thickness of a received covering are found and graphically presented. In the final part of the article, the basic conclusions and recommendations relating to applying the covering by the electro-contact method are formulated. The disadvantages of the given method of components restoration are revealed, and the ways to improve these are offered.